The Influence of Organizational Culture and Principal Leadership on Teacher Performance Through Job Satisfaction and Job Stress in Public Senior High Schools in Jambi Province - Liputo, Muhammad Arif; Suca, Akmal; Muazza, Muazza (Edukasi, 2026)
Teacher performance is an important indicator for assessing the effectiveness of educational management in schools, especially in efforts to improve the quality of education and ensure the sustainability of school organizational management. This study aimed to analyse the influence of organizational culture and principal leadership behavior on teacher performance, both directly and indirectly through job satisfaction and job stress as managerial mechanisms. This study employed a quantitative, explanatory survey design. The study population included all public high school teachers in Jambi Province, totalling 5,105 people, and a sample of 375 people was selected using a cluster random sampling technique. Data were collected through a structured questionnaire and analysed using the Partial Least Squares Structural Equation Modelling (PLS-SEM) method. The results showed that this model has significant explanatory power. The coefficient of determination (R²) of 0.701 indicates that variations in teacher job satisfaction are largely explained by organizational culture and principal leadership behaviour, while job stress has an R² value of 0.670. Teacher performance has an R² value of 0.769, indicating that most of the variation in teacher performance is explained by organizational and psychological factors contained in the model. Organizational culture and principal leadership behaviour were found to have a significant influence on job satisfaction and job stress. Job satisfaction has a positive effect on teacher performance, while job stress has a negative effect, confirming the role of both as important mediating variables. Theoretically, this study strengthens the field of educational management by positioning organizational culture and principal leadership as strategic managerial instruments in improving teacher performance. Practically, these findings suggest that improving teacher performance requires an integrated educational management approach, including strengthening school organizational culture, instructional leadership, and the systematic management of teacher well-being.